2009
DOI: 10.1007/s00784-009-0355-4
|View full text |Cite|
|
Sign up to set email alerts
|

Two-year clinical performance of glass ionomer and resin composite restorations in xerostomic head- and neck-irradiated cancer patients

Abstract: The aim of this study was to evaluate the clinical performance of adhesive filling materials in class V cavities in xerostomic head- and neck-irradiated cancer patients, in terms of marginal adaptation, anatomical form and recurrent caries. We selected 35 high-caries-risk, post-radiation, xerostomic adults with ≥3 cervical carious lesions in the same arch. Every patient received a KetacFil (KF), PhotacFil (PF) and Herculite XRV (HX) restoration. Patients were instructed to use a neutral 1% sodium fluoride gel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
105
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(115 citation statements)
references
References 35 publications
2
105
0
8
Order By: Relevance
“…Conventional GIC or RMGI is useful in caries management because it exhibits chemical adherence and fluoride release 2. RMGI is the material of choice in root surface restoration because light-cured resin polymerization can be used, which allows for immediate setting, improved strength, and esthetic enhancement 1314. RMGI has bonding capacity that enhances its ionic bonding to hydroxyapatite and it exhibits micromechanical interlocking similar to that of conventional GIC 15.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional GIC or RMGI is useful in caries management because it exhibits chemical adherence and fluoride release 2. RMGI is the material of choice in root surface restoration because light-cured resin polymerization can be used, which allows for immediate setting, improved strength, and esthetic enhancement 1314. RMGI has bonding capacity that enhances its ionic bonding to hydroxyapatite and it exhibits micromechanical interlocking similar to that of conventional GIC 15.…”
Section: Discussionmentioning
confidence: 99%
“…En ese trabajo se comenta el escaso conocimiento de la clínica de las lesiones precancerosas que tienen los estudiantes de Odontología de la clínica de la Facultad de Medicina de la Universidad de Lagos, Nigeria. Destacaríamos, igualmente, un trabajo sobre quimioterapia 18 , otro sobre radioterapia de intensidad modulada 19 , otro sobre crioterapia 20 y un ú ltimo sobre té cnicas de restauració n dental 21 .…”
Section: Discusió Nunclassified
“…De Moor et al [48] demonstrated significantly less recurrent caries around Class V GICs compared to resin composites in irradiated patients. This difference was particularly marked when fluoride use was low.…”
Section: Post-radiotherapy Management: Restorative Considerationsmentioning
confidence: 99%
“…p16 negative cases had poorer quality of life, as did current and ex-smokers, with current smokers faring worse. 48 Pre-RT dental extractions by number revealed that >8 were associated with a significantly worse quality of life than those who had no extractions. While 1-7 pre-RT extractions and post-RT extractions were associated with a reduced quality of life, this was not found to be significant at levels applied.…”
Section: Ohip-14mentioning
confidence: 99%
See 1 more Smart Citation